Killing Gay Men, 1976-2001 - Bartlett, Peter (The British journal of criminology, 2007)
The primary claim of this paper is that sufficient consistencies can be shown in the cases studied here and in the related literature that gay sexual homicide constitutes a coherent object of study. That is, in itself a significant finding. Gay men are dying, and the circumstances under which that is taking place warrants analysis in its own right. The cases are of broader intellectual interest, however. The existing literature relating to sexual crime pre-supposes a male assailant and a female victim. This is true both of the sociology of masculinity and also the psychological literature. The cases in this study present sexual crime in a context in which women are absent, and, as such, raise questions about the scope, assumptions and findings of that literature. [ABSTRACT FROM AUTHOR]